Flow Patterns Transition Law of Oil-Water Two-Phase Flow under a Wide Range of Oil Phase Viscosity Condition - Wei Wang; Wei Cheng; Kai Li; Chen Lou; Jing Gong (Journal of Applied Mathematics)
A systematic work on the prediction of flow patterns transition of the oil-water two-phase flows is carried out under a wide range of oil phase viscosities, where four main flow regimes are considered including stratified, dispersed, core-annular, and intermittent flow. For oil with a relatively low viscosity, VKH criterion is considered for the stability of stratified flow, and critical drop size model is distinguished for the transition of o/w and w/o dispersed flow. For oil with a high viscousity, boundaries of core-annular flow are based on criteria proposed by Bannwart and Strazza et al. and neutral stability law ignoring that the velocity of the viscous phase is introduced for stratified flow. Comparisons between predictions and quantities of available data in both low and high viscosity oil-water flow from literatures show a good agreement. The framework provides extensive information about flow patterns transition of oil-water two-phase flow for industrial application.